Assessing the Knowledge and Engagement of Sustainable Development Goals through the Analysis of Educational Quality in Schools: Evidence from Pakistan - Azeem, Mishal; Khan, Huma; Sharjeel, Muhammad Yousuf (Annals of Human and Social Sciences, 2023)
In SDG, role of school-based quality of education and respective examinations play a significant role in the overall development and sustainabiability schools. School-based instructional quality and effective classroom management are tools that assess school students’ academic performance in standardized tests administered by Examining Boards. SDG endeavours provide scores, interpretation of results and sometimes estimate a potential specialization field of students’ skills and ability. This paper examines the extent to which SDGs are able to address the quality of academic performance of students in respective schools across Pakistan whether there was any significant relationship between SDGs and quality of education provided in the schools across Pakistan. The extent to which the SDGs can ascertain the quality of teaching and learning at schools was the major concern on the study. A questionnaire survey comprising items pertaining to the conduct of classes, instructions, classroom experiences of students in schools, benefits, challenges and problems in schools was used in the context of SDG 4. A non-probability sample of n =250 participated in the study. The study employed a survey and responses were coded per the qualitative research paradigm. 92% school teachers and 86% school students affirmed they found quality of school-based instructions and experiences of students were not up to the mark to test the skills and knowledge of school students through Board Examinations. Majority of professional teachers who teach students in schools believe that school cannot directly address the issues and challenges highlighted in SDGs with respect to quality of education. The study results were varied depending on the benefits, barriers and problems in each school. The study found that the SDG-based measures and the quality of education were not effective despite the fact that students take the standardized examinations in their respective Board Examinations.